The structure of the annual migratory flight activity in a songbird - Sjöberg, Sissel ; 0000-0002-1392-7441; MacÍas-Torres, Pablo ; 0000-0002-4503-164X; Andersson, Arne ; 0000-0002-1363-4403; Bäckman, Johan ; 0000-0002-4203-9793; Thorup, Kasper; Tøttrup, Anders Peter; Alerstam, Thomas (Proceedings of the Royal Society B: Biological Sciences, 2025)
Migratory songbirds have an internal circannual genetic programme that controls the timing and extent of migratory flight activity, as demonstrated by experiments with birds held in cages. We used multisensor data loggers to record the timing and duration of all migratory flights during the annual cycle of 15 free-living individuals of red-backed shrikes Lanius collurio. Annual actograms unexpectedly revealed that the nocturnal migratory flights of the shrikes were organized in a highly structured way, with flights aggregated into segments that could be readily identified for all individuals, showing low variability and thus high consistency between individuals. These results suggest that the execution of migratory flights is under a high degree of control according to a rather detailed internal travelling plan for the annual migration cycle. Potentially, the control of migratory flight under natural conditions depends on a complex feedback process where external cues associated with the geographic, temporal and nutritional situation of the bird are required for the internal programme to properly regulate the successive segmental flight steps of the migratory journey. This would mean that the internal/genetic programme for control of bird migration is much more dynamic and complex than hereto assumed.
Publisher Copyright: © 2025 The Authors.
Keywords: accelerometer; biologging; bird migration; circannual programme; flight activity; Lanius collurio; migration programme; songbirds